Underclass and its representations in the contemporary British cinema - Lacková, Petra (2006)
Social reality of working class has become one of the main issues of the roaring debates in Britain following the fall of the conservative party at the end of the 80s. Many have argued about the emergence of a new class, characterised by people who suddenly found themselves being outcastes to the edge of society. Whether this constantly growing group of impoverished people could be easily identified by certain common features and what these features should be is still a part of an unsolved question. The theme of this so-called underclass was popularised by a number of films and books which showed a way this new social phenomena was to be regarded in Trainspotting, dealing with irresponsible and careless drug addicts, became one of the most celebrated items of modern youth culture in Britain. Brassed Off and The Full Monty give us a vibrant and heart-warming picture of working class men who loose their jobs but manage to keep their minds cheerful and their lives full of j